2008
DOI: 10.1111/j.1365-2672.2008.03733.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas fluorescensHYK0210-SK09 offers species-specific biological control of winter algal blooms caused by freshwater diatomStephanodiscus hantzschii

Abstract: Aims:  The study of an algicidal activity and mechanism of the isolated Pseudomonas fluorescens HYK0210‐SK09 (SK09) against a winter bloomed harmful diatom, Stephanodiscus hantzschii. Methods and Results:  SK09 was isolated from the Paldang reservoir, Korea and used to biological control of S. hantzschii. The inoculation of SK09 at the final density of 5 × 106 cells ml−1 caused degradation of >90% of S. hantzschii cells within 5 days. The algal cell lysis was achieved by a direct attack of the bacteria to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 28 publications
2
47
1
1
Order By: Relevance
“…Therefore, the ability to function at a low temperature is an essential requirement for SK09 to express its algicidal activity. The previous study confirmed that SK09 grows well between 10 C and 30 C (Jung et al 2008) and showed the powerful algicidal activity between 5 C and 15 C in the wild (Jung et al 2010(Jung et al , 2013. Thus, it is possible to apply this bacterium to naturally occurring Stephanodiscus blooms.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…Therefore, the ability to function at a low temperature is an essential requirement for SK09 to express its algicidal activity. The previous study confirmed that SK09 grows well between 10 C and 30 C (Jung et al 2008) and showed the powerful algicidal activity between 5 C and 15 C in the wild (Jung et al 2010(Jung et al , 2013. Thus, it is possible to apply this bacterium to naturally occurring Stephanodiscus blooms.…”
Section: Discussionmentioning
confidence: 65%
“…To answer this question, we implemented two mesocosm experiments and studied direct application of immobilized SK09 cells in extremely low temperatures and analyzed the results. Some of the experimental data referred to in this work were obtained in our previous studies (Jung et al 2008(Jung et al , 2009a(Jung et al , 2010(Jung et al , 2013.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations